2015
DOI: 10.1021/acs.jpclett.5b01634
|View full text |Cite
|
Sign up to set email alerts
|

Tuning an Atomic Switch on a Surface with Electric and Magnetic Fields

Abstract: Controllable switching an adatom position and its magnetization could lead to a single-atom memory. Our theoretical studies show that switching adatom between different surface sites by the quantum tunneling, discovered in several experiments, can be controlled by an external electric field. Switching a single spin by magnetic fields is found to be strongly site-dependent on a surface. This could enable to control a spin-dynamics of adatom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In addition to experimental work, a theoretical model for fieldassisted migration has been developed to create atomic gaps between gold nanoelectrodes using ab initio calculations. [278,289] This configuration evaluates gold nanostructures during tension and compression to understand the mechanism. In field-assisted atomic migration (FAAM), the external field provides the driving force, improves the initial energy of the system, reduces the potential barrier in the migration path, and enables atomic migration.…”
Section: Electric Field Driven Atomic Switchmentioning
confidence: 99%
“…In addition to experimental work, a theoretical model for fieldassisted migration has been developed to create atomic gaps between gold nanoelectrodes using ab initio calculations. [278,289] This configuration evaluates gold nanostructures during tension and compression to understand the mechanism. In field-assisted atomic migration (FAAM), the external field provides the driving force, improves the initial energy of the system, reduces the potential barrier in the migration path, and enables atomic migration.…”
Section: Electric Field Driven Atomic Switchmentioning
confidence: 99%
“…Despite its macroscopic origin, it has been shown that this equation is useful for studying the magnetization dynamics of nanostructures. [37][38][39][40][41] The LLG equation adapted for atomic-scale systems can be written as 42…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…External control of adsorbate motion on surfaces is interesting both for the fundamental understanding of the mechanisms in play, and for the development of novel nanoscale devices. Possible technical applications include, e.g., functional nanostructures designed by areaselective atom deposition [1], atomic/molecular switches [2,3] or ion traps based on electric fields, such as Paul traps [4], which are important for quantum computing.…”
Section: Introductionmentioning
confidence: 99%